Anaerobic training with ballistic exercise using different durations of exercise and rest interval - Smilios, I.; Christou, M.; Nikas, T.; Mantzouranis, N.; Tokmakidis, S. P. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the study was to examine the effects of exercise set duration and rest intervals during the performance of loaded squat jumps (LSJ) sessions oriented for the improvement of anaerobic performance. Summary: It appears that when the duration of repeated exercise sets increases, performance decrement is greater regardless if the exercise to rest ratio is kept the same. The higher activation of anaerobic metabolism requires probably, a longer exercise to rest ratio for the restoration of the intra-muscular environment at a level comparable to that achieved with a shortest exercise duration and rest interval. Performance in a single maximal effort, like a countermovement jump, does not appear to be affected by the exercise to rest ratio. However, in repeated efforts, such as sets of continues vertical jumps, the shortest the rest interval the greatest the decrease in performance.